Fluctuating Asymmetry in the Polymorphic Sand Cricket (Gryllus firmus): Are More Functionally Important Structures Always More Symmetric? - Matthew R. Whalen; Krista J. Chang; Alexandria B. Jones; Gabriel Rivera; Amy M. Worthington (Insects, 2022)
Fluctuating asymmetry (FA) may serve as a reliable indicator of the functional importance of structures within an organism. Primary locomotor structures often display lower levels of FA than other paired structures, highlighting that selection can maintain symmetry in fitness-enhancing traits. Polyphenic species represent an attractive model for studying the fine-scale relationship between trait form and function, because multiple morphs exhibit unique life history adaptations that rely on different traits to maximize fitness. Here, we investigated whether individuals of the wing polyphenic sand field cricket (Gryllus firmus) maintain higher levels of symmetry in the bilateral structures most vital for maximizing fitness based on their specific life history strategy. We quantified FA and directional asymmetry (DA) across a suite of key morphological structures indicative of investment in somatic growth, reproduction, and flight capability for males and females across the flight-capable longwing (LW) and flight-incapable shortwing (SW) morphs. Although we did not find significant differences in FA across traits, hindwings lacked DA that was found in all other structures. We predicted that functionally important traits should maintain a higher level of symmetry; however, locomotor compensation strategies may reduce the selective pressures on symmetry or developmental constraints may limit the optimization between trait form and function.